The Role of Brand Trust in Mediating the Relationship Between Brand Image and Brand Loyalty among Cosmetic Users - Janah, Linda Maulidatul; Hasyim (Yayasan Gema Bina Nusantara, 2025)
This study aims to analyze the influence of brand image and brand trust on brand loyalty among Somethinc cushion cosmetic users. With increasing competition in the cosmetics industry, it is important for companies to understand the factors that influence customer loyalty. The research method used is quantitative with data collection through questionnaires distributed to 140 respondents in the Greater Jakarta area. Data analysis was conducted using Partial Least Square-Structural Equation Modeling (PLS-SEM) to test the relationship between variables. The results show that brand image has a positive and significant influence on brand trust, which in turn has a positive impact on brand loyalty. This finding indicates that companies need to focus on developing a strong brand image and building consumer trust to increase loyalty. This study also identified that customer experience and product quality play an important role in shaping brand image and trust. The managerial implications of this study suggest companies to implement effective and sustainable marketing strategies to retain and attract more customers.